Quantitative test method for evaluation of anti-fingerprint property of coated surfaces - Xuan, D. T. T. (2013)
An artificial fingerprint liquid is formulated from artificial sweat, hydroxyl-terminated polydimethylsiloxane and a solvent for direct determination of anti-fingerprint property of a coated surface. A range of smooth and rough surfaces with different anti-fingerprint (AF) properties were fabricated by sol–gel technology, on which the AF liquid contact angles, artificial fingerprint and real human fingerprints (HF) were verified and correlated. It is proved that a surface with AF contact angle above 87° is fingerprint free. This provides an objective and quantitative test method to determine anti-fingerprint property of coated surfaces. It is also concluded that AF property can be achieved on smooth and optically clear surfaces. Deep porous structures are more favorable than bumpy structure for oleophobic and AF properties.